The effect of murottal Al-Quran therapy on pain intensity and oxygen saturation in active phase parting women - Yustiari, Yustiari; Wahida, Wahida; Anwar, Khalidatul Khair; Naningsi, Hasmia; Asi, Melania; Saraswati, Endah (International Journal of Public Health Science (IJPHS), 2024)
Anxiety in women increases with the start of labor and has a negative impact on mothers and newborns. The aim of this study was to determine the effect of listening to murottal Al-Quran on increasing oxygen saturation and reducing pain in mothers in the active phase of labor. This research was quantitative research with a quasi-experimental design and a preexperimental design one-group pretest-posttest. This study was conducted at the Kendari City Hospital. The sample was determined as a total population, considering that the number of mothers during the first active phase was only 30. The data analysis technique in this study went through two calculation stages: the data normality test by Kolmogorov-Smirnov, Paired Sample Statistics, and all calculations using SPSS. The results of the statistical tests using the Wilcoxon test yielded a p-value of 0.000. Statistically, it can be concluded that there are differences in oxygen saturation values before and after the administration of murottal intervention. It was also found that 27 respondents experienced an increase in oxygen saturation after receiving murottal intervention. In conclusion, murottal intervention increased oxygen saturation.